RANCANG BANGUN SISTEM INFORMASI BACK OFFICE (SIBO) BERBASIS WEBSITE PADA PT JABAR LAJU TRANSINDO MENGGUNAKAN METODE RAD (RAPID APPLICATION DEVELOPMENT) - Aris Setyawan (2022)
The importance of the back office role in a company has a great influence, this activity includes recording, transaction history, and reporting. However, with the development of technology at this time, back-office activities at PT Jabar Laju Transindo still use the manual method, namely by still using Microsoft Excel and recording for managing company data. This research was conducted to create a back-office information system that can support the work process of the marketing division at PT Jabar Laju Transindo in producing better recording reports in terms of visual delivery and presentation of recording information. The method that will be used in building this information system is using the RAD (Rapid Application Development) method. The system built in the form of a website has several modules or you could say features, these modules include wheel bin, contracts, schedules, contract reports, manifest reports, recapitulation reports, and many more. This system also has a login module to be able to protect data to be more secure, in addition to protecting data more optimally this system also stores data in the PostgreSQL database. With the hope, through this back-office information system, can produce reports with visualization in the form of tables and charts and make it easier for readers to read the available reports.